LabVIEW-based learning platform - Sun, Xin (2015)
As Singapore is moving towards the smart city, urban traffic is emerging so as to accommodate the rapidly growing traffic demand. The optical technology could provide an alternate solution to relieve the traffic pressure and improve the road safety. In this project, it aims to design and realize visible light communication through free space using laser beam. The transmitter and receiver can be implemented to the simulated traffic environment as extra modules. It makes the traffic lights not rigidly adhere to signal, but capable of transmitting information to the vehicles. The implementation of this project required the integration and optimization of hardware and software parts. Arduino Uno is leveraged to control the operation of the traffic light system. And additional initiative has been done to improve and perfect the intelligent transport system. Technically, the objective of this project has been achieved and the noise optimization is discussed in the latter chapter. Based on that, this project can serve as a learning platform to the existing course EE2073, which introduces to the students the rudimentary knowledge in the photonics and optics field.